Alterações nas propriedades físicas de um latossolo vermelho-escuro sob diferentes culturas - Cavenage, A. [UNESP]; Moraes, M. L. T. [UNESP]; Alves, M. C. [UNESP]; Carvalho, M. A. C. [UNESP]; Freitas, M. L. M. [UNESP]; Buzetti, S. [UNESP] (Sociedade Brasileira de Ciência do Solo, 1999)
The present work had the objective to analyze the alterations of the physical properties of a dark-red Latosol (typic acrustox), under different use systems. In 1996, samples of soils were collected, under corn crop, pinus, eucalyptus, pasture, ciliary forest (after 10 years of cultivation), and native cerrado vegetation, in three depths (0,00-0,10; 0,10-0,20, and 0,20-0,40 m), in the experimental station from Faculdade de Engenharia de Ilha Solteira - UNESP, located in Selvíria county (MS). The experimental design was the totally randomized, with 18 treatments and 10 replications. In the different treatments the macroporosity, microporosity, total porosity, bulky density, texture, and resistance to penetration were determined. By the results we may conclude that alterations of the physical properties of the soil occurred in the different areas, compared to natural condition; the area with ciliary forest and pinus are closer to the natural conditions, presenting an accommodation of the superficial layer; the other areas of the soil; the areas presented greatest alterations in depths of the 0,00-0,10 m, except for the area with annual crop.

O presente trabalho objetivou analisar as alterações das propriedades físicas de um Latossolo Vermelho-Escuro, sob diferentes culturas e sua capacidade de recuperação. No ano de 1996, foram coletadas amostras de solos sob vegetação de milho, pinus, eucalipto, pastagem e mata ciliar, após 10 anos de cultivo, e cerrado (condição natural), em três profundidades (0,00-0,10; 0,10-0,20 e 0,20-0,40 m), em áreas pertencentes à Fazenda de Ensino e Pesquisa da Faculdade de Engenharia de Ilha Solteira - UNESP, localizada no município de Selvíria, MS. O delineamento experimental utilizado foi o inteiramente casualizado, com 18 tratamentos e 10 repetições. Nos diferentes tratamentos, determinaram-se macroporosidade, microporosidade, porosidade total, densidade do solo, análise granulométrica e resistência à penetração. Com base nos resultados, concluiu-se que ocorreram alterações nas propriedades físicas do solo, quando se compararam os diferentes usos com a condição natural; as áreas com mata ciliar e pinus foram as que mais se aproximaram das condições naturais, apresentando, porém, compactação na camada superficial; as áreas apresentaram maior alteração na profundidade de 0,00-0,10 m, com exceção da área com culturas anuais.
Alterations of the physical properties of a dark-red latosol (typic Acrustox) under different crops
Keywords: cerrado; densidade do solo; porosidade; resistência à penetração; manejo; cerrado; bulky density; porosity; resistance to penetration; management